Low applicatives in Catalan: the case of 'veure-hi' - Cristina Real Puigdollers (Borealis: An International Journal of Hispanic Linguistics)
This paper analyzes an argument structure alternation found in Catalan in which a verb of perception appears with a non-referential locative pronominal clitic hi. In this alternation, a transitive verb like veure ‘to see’ can combine with the pronoun hi and form a stative intransitive predicate veure-hi, which means ‘to be able to see’, and with a reflexive pronoun es, as in veure-s’hi, which has a similar meaning plus an inchoative interpretation. This paper analyzes this alternation within the argument structure framework laid out by Wood and Marantz (2017). Specifically, I propose that the locative pronoun hi and the reflexive pronoun es are the exponents of expletive pronouns associated with identity functions that license different values of a single argument introducer head, i*. In the former case, hi appears in the complement position of i*, which gets a low applicative head interpretation, and the latter in the specifier position of a Voice functional head. With this approach, the paper paves the way for a unified approach to the different values that the locative pronoun hi can display in Catalan.